Approaches to coastal wetland restoration : Northern Gulf of Mexico - Turner, R. E. (Robert Eugene), 1945- (SPB Academic Pub., 2002)
Wetlands Lost The 1,879 thousand hectares of coastal wetlands in the Gulf of Mexico (GOM) comprise 58% of the U.S. coastal wetland total (Turner and Gosselink 1975). These wetlands occur in every GOM state, although two-thirds of the GOM total are in Louisiana, and are typically associated with estuaries, bays, rivers, and the lee-side of barrier islands. The objective of this book is to facilitate and encourage the restoration of these and other wetlands by reviewing the details of construction and costs (which can range from 1 to 45,000 per hectare), and by evaluating case studies for levels.